Cytoskeleton imaging of colorectal and lung cancer spheroids using light sheet microscopy - Sonia Prado-López; Massih Foroughipour; Klaus Becker; Seyed Meraaj Foroughipour; Lukas Weber; Heinz Wanzenboeck; Nika Sarem; Saiedeh Saghafi (BJC Reports)
Abstract Background Three dimensional tumoral models are essential to study cancer biology as they better mimic the complexity of the tumoral masses in vivo. However, to study cancer 3D models’ dynamics new technological approaches are required. Most of the deaths related to cancer are caused by metastasis but still many of the metastatic driving processes remain unknown. A fundamental player in the metastatic process is the cytoskeleton. The polymerization of actin monomers in filaments, known as F-actin, is crucial for cell motility. Also, it can be used to detect necrosis, since F-actin is exposed on necrotic cells due to the loss of the cell membrane’s integrity. To date, studies of actin dynamics in cancer cells have primarily relied on simplistic 2D models and fluorescence microscopy. Methods In this paper, we propose combining light sheet fluorescence microscopy (LSFM) with colorectal cancer (CRC) and non-small cell lung carcinoma (NSCLC) spheroids to study F-actin distribution and exposition with minimal distortions. Results We identified 6 different areas of F-actin intensity that could be correlated with the proliferative, senescence and necrotic zones previously described in cancer spheroid models in vitro. Conclusions Our findings proved the power of the proposed LS meso aspheric optics approach to visualize and quantify F-actin in 3D cancer models with a high level of detail. Importantly, our findings also facilitate the assessment of the necrotic area's extent, clearing the path for improved anti-metastatic treatments and more accurate patient prognosis evaluation.